Quality analysis of marketed seeds of some crops in Nepal - Thapa, M (Agronomy Journal of Nepal, 2013)
Seed samples from seed traders were collected for the three fiscal years (2007/08, 2008/09 and 20009/10) from thirty-nine districts of Nepal. A total of 206 samples from fourteen districts in 2007/08, 206 samples from seventeen districts in 2008/09, and 208 samples from twenty- five districts in 2009/10 were collected for analyzing quality of marketed seeds of crops. Seed samples were collected from the districts where seed act of Nepal was implemented and from where it was not implemented as well. These samples were tested for germination and physical purity in each year separately. Germination percent was determined by top of the paper (TP), between the paper (BP) and sand as recommended for crops/varieties. Percentage of physical purity of seed was measured by separating inert matter, weed seeds, and other crop seeds from seed sample. Percentage of each component was determined by weight basis. From the analysis it was found that quality standard of sold vegetable seeds in market was not improved with respect to germination. Likewise, marketed seed quality of vegetables such as onion, cauliflower, sponge gourd, ridge gourd, bitter gourd, broccoli, cabbage, radish, tomato, chilly, brinjal, Ghiusimi, and mustard were found deteriorated each year. However, physical purity of almost all samples each year was recorded satisfactory. There was no difference on quality of seeds with respect to the districts implementing and not implementing seed act. Of the seed quality standard, germination percentage was the most important attribute that should be considered so far as seed quality standard is concerned. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7530 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.149-156